SELEKSI DAN HIBRIDISASI LONTAR [SELECTION AND HYBRIDIZATION OF PALMYRA] - Tulalo, Meity; Mawardi, Sukmawati; Mahayasa, Nyoman; Wagiman, Fransiskus Xaverius; Novarianto, Hengky (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
Palmyra palm (Borassus flaballifer, L) is a specific crop in dry climate dry land. The purpose of this research is to select the male and female parent Palmyra trees, hybridization, germination and nursery of Palmyra hybrids. The research was carried out on Sabu Island, Sabu Raijua Regency, East Nusa Tenggara Province from 2017 to 2018. The research method was carried out by determining the population of lontar, followed by selection of female and male palm trees, experiments on collecting male flowers and pollen processing on male Palmyra trees. In the female palm tree, fruit bunches are selected that have not been receptive, when receptive and hybridization until the fruit is physiologically ripe, the pollination is controlled using a spout. The results of the selection of the parent palm trees obtained 28 selected parent trees female Palmyra and 12 selected parent trees male Palmyra. The average height of female selected parent trees is 6.67 m and male selected parent trees are 5.08 m. The observations found that the diversity of the number of female flowers between 9-35 fruits/bunches The percentage of fruit so this artificial cross is 54.90%. Mature fruits ready-to-harvest are obtained around 5-6 months after pollination. As many as 77.20% of the hybrid Palmyra palm seeds that are germinated grow and are ready to be planted at 7 months after germination. ABSTRAKTanaman lontar (Borassus flaballifer, L) merupakan tanaman spesifik di lahan kering iklim kering. Tujuan penelitian adalah melakukan seleksi pohon induk lontar jantan dan betina, melakukan hibridisasi, perkecambahan dan pembibitan lontar Hibrida. Penelitian dilaksanakan di pulau Sabu, Kabupaten Sabu Raijua, Provinsi Nusa Tenggara Timur sejak tahun 2017 sampai 2018. Metode penelitian dilakukan dengan menetapkan populasi lontar, seleksi pohon induk lontar betina dan jantan dilanjutkan dengan pengumpulan bunga jantan serta prosesing polen. Pada pohon lontar betina dilakukan seleksi tandan buah yang belum reseptif, saat reseptif dan hibridisasi sampai buah matang fisiologis melalui penyerbukan secara terkontrol menggunakan kerodong. Hasil seleksi pohon induk lontar diperoleh 28 pohon induk terpilih (PIT) lontar betina dan 12 pohon induk terpilih (PIT) lontar jantan. Rata-rata tinggi pohon induk terpilih betina yaitu 6,67 m dan pohon induk terpilih jantan 5,08 m. Hasil pengamatan ditemukan keragaman jumlah bunga betina antara 9-35 buah/tandan. Persentase buah jadi persilangan buatan ini adalah 54,90%. Buah matang siap panen diperoleh sekitar 5-6 bulan sejak polinasi. Sebanyak 77,20% dari benih Lontar hibrida yang dikecambahkan tumbuh dan siap ditanam pada umur 7 bulan setelah dikecambahkan.